Transformasi Layanan Perpustakaan Di Masa Pandemic Covid 19: Studi Kasus di Perpustakaan Universitas Teknokrat Indonesia - Rahmat Iqbal; Eni Amaliah; Khabib Mashudi; Ghalih Perkasa (Ikatan Pustakawan Indonesia, 2021)
Libraries as one of the public information services must also implement health protocols during the Covid-19 pandemic. Libraries limit their services by various rules. Based on a circular letter, the Minister of Education and Culture of the Republic of Indonesia has issued a circular regarding Online Learning and Working from Home in the Context of Preventing the Spread of Corona Virus Disease (COVID-19), and strengthened by a Circular Letter from the Governor of Lampung regarding the Implementation of Controlling the Impact of Corona Virus Disease 2019 ( COVID-19) In Religious, Economic, and Cultural Activities in Lampung Province, the Indonesian Technocrat University Library (UTI) in Bandar Lampung implemented several service policies during the Covid-19 pandemic, including restrictions on direct face-to-face services by only opening online services. , always apply the 3M (Washing hands, Wearing masks and Maintaining Distance) and free online libraries. The study used a literature study type of research method. The approach used in this study is a qualitative-inductive approach, where this approach uses a qualitative method that focuses on literature review. Of the 3 variables, 21 indicators and 100 samples produced quite good results, including reading material variables with an average number of 4.38 out of 8 questions, the second with infrastructure variables with an average number of 4.38 out of 7 questions and three with HR competency variables with the average score is 4.41 out of 6 questions. With a total average of three variables totaling 4.39 with 21 questions. In conclusion, the Indonesian Technocrat University community does not find it difficult to access digital collections or enjoy the services the library provides during a pandemic, a possible reference source that can be accessed when undergoing online lectures from home. Digital information is one of the most possible alternatives to overcome the problem of miscommunication between librarians and users. The digital promotional information model is needed by transferring promotional information materials using digital technology, and utilizing social media, such as Youtube, Whatsapp, websites and Facebook as media for publication and promotion.